Youth cyberfeminism: Issues for our times - Sousa , Karinna Alves Amorim de; Monte , Liana Maria Ibiapina do; Silva , Maria Luisa Pires da; Júnior , Paulo de Tarso Xavier Sousa; Nascimento , Elaine Ferreira do (Seven Editora, 2023)
The last decade has seen an increase in the articulation of social movements, using the media and especially virtual communication networks as a resource for the dissemination of their agendas. The feminist movement has also been occupying these spaces and showing the possibility of communicating and reaching audiences that they could not reach before. Through these new information technologies and dialogues, which allow the production, access, and dissemination of information between subjects, even if they are physically distant, it was possible to strengthen activism during the period of the Covid-19 pandemic, when social distancing and isolation became mandatory. DOI:https://doi.org/10.56238/alookdevelopv1-128